Influence of Nutritional Intake and Exclusive Breastfeeding History on the Incidence of Stunting in Children Aged 12-24 Months in Deli Serdang Regency - Lubis, Rahmi Amelia; Aritonang, Evawany Yunita; Sudaryati, Etti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research chose children aged 12-24 months as the sample because they are in a critical period of physical and cognitive growth, vulnerable to stunting due to inadequate nutritional intake. Other research shows that inadequate nutritional intake at 6-24 months of age can affect brain development and a child's future intelligence. It is important to monitor the nutritional intake and nutritional status of children aged 12-24 months to reduce the risk of stunting and its negative impact on cognitive development. Additionally, at this age, exclusive breastfeeding plays a crucial role in child growth, and this research can help understand the relationship between exclusive breastfeeding, nutritional intake, and stunting in children aged 12-24 months.